Top 100 #PCOS influencers: Understanding who, why and how online content for PCOS is influenced - Elhariry, Maiar; Malhotra, Kashish; Solomon, Michelle; Goyal, Kashish; Kempegowda, Punith (Frontiers in Endocrinology, 2022)
Background: With the exponential increase in digital space of social media platforms, a new group called social media influencers are driving online content of polycystic ovary syndrome (PCOS) which eventually influences behaviour and decision-making process. The objective of this study was to identify the top 100 social media (Twitter) influencers and organizations from across the globe who are advocating for PCOS. We further explored the origin and journey of these social media influencers. Methods: We identified the top 100 PCOS influencers and organizations between July and August 2022 using three social network analysis tools- Cronycle, Symplur and SocioViz. These influencers were invited to a semi-structured interview to explore why they chose to become an influencer and the support they have to deliver their online content. Two independent authors coded the anonymised transcripts from these interviews and broad themes were identified by thematic inductive analysis. Results: 95.0% of individual influencers and 80% of organisations are from high-income countries. Most influencers in our study agree that social media is an essential tool in the present day to raise awareness of PCOS. However, they reiterated social media also has significant disadvantages that require consideration and caution. Most influencers were driven by poor personal experience and worked voluntarily to reduce misinformation and improve the experiences of women diagnosed with PCOS in the future. Although there is an interest in working together, there is currently minimal collaborative work between influencers. Conclusion: There is a global inequity of #PCOS influencers online. Establishing standards and support based on evidence may help develop more influencers, especially in low- and middle-income countries, so we can counter misinformation and provide locally acceptable guidance.